PENGARUH TERPAAN MEDIA TERHADAP MINAT MASYARAKAT MENGIKUTI AJANG PENCARIAN BAKAT INDONESIA IDOL (STUDI PESERTA AUDISI DI JAKARTA) - Romi Syahril; Robbikal Muntaha Meliala (Jurnal Akrab Juara, 2019)
The phenomenon of the new artist's life especially from the world Pull sound (Singing) which is widely preached media, giving influence of its own interest for the audience. Indonesian Idol is a talent search program in the field of drag votes that provide inspiration for the growing interest to become a singer artist especially among teenagers. The purpose of the study is to determine the influence of media exposure to public interest following the Idol Indonesia talent search event. This study uses SOR theory to describe the exposure of the media to public interest following the Idol Indonesian talent search event. This study was conducted in a survey among participants of audition jakarta the number of respondents 100 people. The results showed that media exposure positively affect the interest of the community following the Idol Indonesian talent search event by 30.2%. So if media exposure is increased then the interest of the community following the Idol Indonesian talent search event also increased